IMPLEMENTATION OF LOCAL WISDOM: PENERAPAN ORNAMEN KAIN SONGKET PALEMBANG PADA BANGUNAN, RUANG PUBLIK DAN INFRASTRUKTUR DI KOTA PALEMBANG - Muhammad Fathur Hidayat; Agung Budi Sardjono Sardjono (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2025)
Abstract: The city of Palembang, as the capital of South Sumatra Province, is known as a center of cultural acculturation between Malay, Middle Eastern and Chinese cultures, reflected in various aspects of life, including architecture and traditional culture. One of the most prominent cultural heritages is the Palembang Songket Fabric, which serves not only as traditional attire but also as a symbol of social status, luxury and cultural identity from the Sriwijaya Kingdom era to the present day. The motifs on the songket fabric, such as bungo tanjung, pucuk rebung, bintang berante and nago besaung, carry deep philosophical meanings, symbolizing the values of life, hope, social harmony and the hospitality of the people of Palembang City. In the context of architecture, songket fabric ornaments have been widely adapted and applied to buildings, public spaces and infrastructure in Palembang City as a form of preserving local wisdom and strengthening the city's identity. This study employs a qualitative descriptive method through field observations, literature reviews and case studies on architectural objects incorporating songket fabric motifs. The findings reveal that the application of songket fabric ornaments enhances the city's visual appeal, boosts community pride, and reinforces Palembang City's branding as a cultural city. However, challenges remain, particularly regarding the authenticity of motifs and the preservation of philosophical values amid modernization. Therefore, collaboration between the government, community, cultural practitioners and architects is essential to ensure that the application of songket motifs is not only visually appealing but also remains authentic and meaningful as a living and relevant cultural heritage in the era of globalization. Keyword: Local Wisdom, Ornament, Palembang Songket Fabric Abstrak: Kota Palembang, sebagai ibu kota Provinsi Sumatera Selatan, dikenal sebagai pusat akulturasi budaya Melayu, Timur Tengah dan Tionghoa yang tercermin dalam berbagai aspek kehidupan, termasuk arsitektur dan kebudayaan tradisional. Salah satu warisan budaya paling menonjol adalah Kain Songket Palembang, yang tidak hanya berfungsi sebagai busana adat, tetapi juga simbol status sosial, kemewahan dan identitas budaya sejak masa Kerajaan Sriwijaya hingga kini. Motif-motif pada kain songket, seperti bungo tanjung, pucuk rebung, bintang berante dan nago besaung, mengandung makna filosofis yang mendalam, melambangkan nilai-nilai kehidupan, harapan, keharmonisan sosial dan keramahtamahan masyarakat Kota Palembang. Dalam konteks arsitektur, ornamen kain songket diadaptasi dan diaplikasikan secara luas pada bangunan, ruang publik dan infrastruktur di Kota Palembang, sebagai bentuk pelestarian kearifan lokal dan penguatan identitas kota. Penelitian ini menggunakan metode deskriptif kualitatif melalui observasi lapangan, studi literatur dan studi kasus pada objek-objek arsitektur yang menerapkan motif kain songket. Hasil penelitian menunjukkan bahwa penerapan ornamen kain songket memperindah visual kota, meningkatkan kebanggaan masyarakat, serta memperkuat branding Kota Palembang sebagai kota budaya. Namun, tantangan tetap ada, terutama terkait keaslian motif dan pelestarian nilai filosofis di tengah modernisasi. Oleh karena itu, kolaborasi antara pemerintah, masyarakat, pelaku budaya dan arsitek sangat diperlukan agar penerapan motif songket tidak hanya indah secara visual, tetapi juga tetap otentik dan bermakna sebagai warisan budaya yang hidup dan relevan di era globalisasi. Kata Kunci: Kearifan Lokal, Ornamen, Kain Songket Palembang